Pengembangan Desain Kursi Santai Lipat Dengan Metode Quality Function Deployment (QFD) - Bahar, Yustar Afif; , Siti Nandiroh,ST,.M.Eng; , Ir.Muchlison Anis,MT (2016)
Nowadays, plenty of lounge chairs are made of wood, laid over, and aluminum with a design that is diverse as well. However, there are still companies chair products (casual fold) less attention to aspects of ergonomics, efficiency, and versatility. Therefore, it is necessary to use methods of customer needs with Quality Function Deployment is commonly abbreviated to QFD. This study aims to determine: (1) Make a lounge chair folding design, (2) Mendikripsikan attributes include the attributes of consumer needs functionality, ergonomics, materials, and beauty. (3) to analyze the method of Quality Function Deployment (QFD) in the House of Quality. (4) To understand and apply the QFD method in planning the design of chairs folding chairs in order to produce according to customer needs. The study was conducted in Kalurahan Madegondo Solo Baru, Grogol, Sukoharjo, with a sample of 48 people. Methods of data analysis using QFD. Conclusion of the study, namely: (1) The attributes that are considered important by consumers on the quality of product design folding chairs, consisting of attribute functionality, ergonomics, materials, and beauty. (2) The order of the interests of consumer needs, namely: (a) the chair to relieve tired, (d) seats there is a support, (c) the chair has a texture almost the same as the curvaceous body, (d) the chair can be used comfortably, and (e) seat angle of more than 90o. (3) The attributes that need to be considered as a technical requirement maker, which is the standard for the use of the lounge chairs are ergonomic and materials as desired by the product manufacturer, wood, iron, or stainless steel.